(untitled) (Medico Legal Update, 2021)
Background: Hypertrophied inferior turbinates are the frequent cause of nasal obstructions.Microdebridor is one of recent advances in technology used for reduction of hypertrophied turbinate to improve nasal breathing. Objective: To evaluate and compare the effectiveness of microdedrider assisted inferior turbinoplasty on nasal breathing, turbinate size and complications according to the pathological causes. Patients and Method: Aprospective case study of 45 patients with chronic nasal obstruction and hypertrophied inferior turbinates underwent microdebrider assisted tubinoplasty. At Salah-eldeen General Hospital and private practice in salah-eldeen governorate, Iraq. During the peroid from June 2016-June 2018. The patients were classified according to the cause of turbinate hypertophy and follow up at 1,3, and 12 months post operatievly for nasal bereathing and turbinate size.Results : The preoperative turbinate size was grade III (48.5%) and grade IV (51.5%). At 1,3,and 12 months post operatively, the grade I and II was (87%). (90%), and (84%) respectively better in compensatory hypertrophy. The subjective patient’s satisfaction grade I(relieved) and II(improved)) at 1,3, and 12 month after surgery was (100%) (97%) and (89%) respectively more satisfaction with compensatory hypertrophy. Conclusion: The therapeutic success of microdebrider turbinoplasty for improvement of nasal obstruction and turbinate size, according to the causes . In early postoperative period was almost equal,but long-term follow-up (one year) found it was greater in compensatory hypertrophy and chronic rhinosinusitis and less in allergic and nonallergic rhinitis. There is no significant association between the cause of turbinate hypertrophy and type of complications.